2009
DOI: 10.1017/s2040174409990043
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and vascular disease prior to hatching in chick embryos incubated at high altitude

Abstract: The partial contributions of reductions in fetal nutrition and oxygenation to slow fetal growth and a developmental origin of cardiovascular disease remain unclear. By combining high altitude with the chick embryo model, we have previously isolated the direct effects of high-altitude hypoxia on growth. This study isolated the direct effects of high-altitude hypoxia on cardiovascular development. Fertilized eggs from sea-level or high-altitude hens were incubated at sea level or high altitude. Fertilized eggs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…Several studies have now reported in mammalian and nonmammalian species that chronic developmental hypoxia can lead to an increase in the wall-to-lumen thickness or area ratio [27,28,33,34]. On the basis of hemodynamics, Folkow [47] stressed a role for an increased vascular wall-to-lumen ratio to be associated with an increase in resistance to flow and, thereby, an increase in perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have now reported in mammalian and nonmammalian species that chronic developmental hypoxia can lead to an increase in the wall-to-lumen thickness or area ratio [27,28,33,34]. On the basis of hemodynamics, Folkow [47] stressed a role for an increased vascular wall-to-lumen ratio to be associated with an increase in resistance to flow and, thereby, an increase in perfusion pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have employed the chick embryo as an animal model in an attempt to isolate the effects on growth and the developing cardiovascular system of chronic hypoxia, independent of changes in maternal nutrition and of the physiology of the mother and the placenta [28,29,30,31,32,33,34]. In mammals, only one previous study reported the relative contributions of developmental hypoxia and undernutrition to fetal alterations in somatic growth and cardiovascular structure and function in the rat [27].…”
Section: Introductionmentioning
confidence: 99%
“…These responses were coupled with pump dysfunction, decreased ejection fractions, and diastolic dysfunction, which persisted in adulthood. Further, Salinas et al showed marked cardiovascular morphostructural changes in high-altitude chicks, which were reverted either by incubation at low altitude or by oxygen supplementation [26]. Notably, Herrera et al followed up these chicks to adulthood describing cardiac impairment in the capacity to response to pressor challenges [27].…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%
“…Using avian models of FGR has served to establish that chronic hypoxia, independent of nutrition, plays a crucial role in vascular programming [30,31]. Studies of vascular function during fetal life show remarkable similarities between the effect of hypoxia in chick embryos and placental insufficiency in mammals [26,28]; they have also served to assess the long-term consequences [27]. In both cases (chick embryos and mammalian fetuses), the presence of endothelial dysfunction and vascular remodeling is observed mainly in peripheral arteries.…”
Section: Hypoxia and Oxidative Stress In Fgrmentioning
confidence: 99%
“…It has been reported that chronic gestational hypoxia increases fetal cardiac afterload, which places strain on the heart and associated vessels. As a result, ventricular aortic thickening has been reported in chicks (Rouwet et al, 2002;Salinas et al, 2010) and rats exposed to chronic prenatal hypoxia Giussani et al, 2012b).…”
Section: Effects Of Prenatal Hypoxia On the Heartmentioning
confidence: 99%